1988
DOI: 10.1136/adc.63.12.1434
|View full text |Cite
|
Sign up to set email alerts
|

IgG subclass deficiency in asthma.

Abstract: SUMMARY Total immunoglobulin G (IgG) and subclasses were measured in serum samples from 82 children with chronic asthma, aged 1*5 to 6-3 years, and 76 controls. Concentrations of IgGj, IgG2, IgG3, and total IgG were significantly lower in asthmatic children aged 1 to 5, and IgG2 concentrations were also significantly lower in asthmatic children over 5 years of age. Twenty eight asthmatic children had at least one value in the deficient range, and 26 had IgG2 deficiency alone or in combination. Five children ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
2

Year Published

1989
1989
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 10 publications
3
19
0
2
Order By: Relevance
“…The broad inhibitory actions of FcgRIIb in hASM are consistent with a role for this receptor in the beneficial effects of FcgR ligands implied by association of asthma severity and low IgG levels (7,8). It is unclear whether FcgR expression is disrupted in disorders such as asthma.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The broad inhibitory actions of FcgRIIb in hASM are consistent with a role for this receptor in the beneficial effects of FcgR ligands implied by association of asthma severity and low IgG levels (7,8). It is unclear whether FcgR expression is disrupted in disorders such as asthma.…”
Section: Discussionmentioning
confidence: 66%
“…Several studies have shown an IgG deficiency in asthma, with low levels of IgG being associated with the severity of the asthmatic symptoms (7,8). This may reflect diminished capacity to neutralize allergens, thus enabling more effective IgE/FceR activation (1).…”
mentioning
confidence: 99%
“…Patients who fit these descriptions are occasionally found to have antibody deficiency. [126][127][128][129][130][131][132][133] In some patients with immune abnormalities and infection-associated asthma, replacement doses of IGIV might eliminate the triggering infections, reduce the frequency and severity of their pulmonary symptoms, or both. This in turn might decrease the symptoms and morbidity of asthma.…”
Section: Use Of Igiv In Asthmamentioning
confidence: 99%
“…Within an adult patient population with chronic bacterial respiratory infections, an isolated IgG1 subclass deficiency can be found [10][11][12][13][14], but normal IgG1 levels are also described in these patients [15,16].…”
Section: Introductionmentioning
confidence: 99%